Leverage and profitability comparison analysis pre and post merger (study on company registered in indonesia stock exchange 2000-2017 period) - Budhi Pamungkas Gautama; Diinan Nur Khulaidah (INOVASI, 2022)
This research was conducted to analyze the differences in leverage and profitability ratios pre and post the merger of companies listed on the Indonesia Stock Exchange in 2000-2017. The method used in this research is descriptive and verification using hypothesis testing. Samples were collected based on purposive sampling which resulted in 38 companies and the analytical tools used include descriptive analysis, normality using the One-Sample Kolmogorov-Smirnov Test, and Hypothesis using the Wilcoxon Signed Rank. The data used are secondary data of DER and ROE on companies conducting the merger listed on the Indonesia Stock Exchange. The timing of the analyzes carried out by this study was two years pre and two years post the merger. The results of this study indicate that the development of Leverage (DER) fluctuates and tends to increase, inversely proportional to the decline in profitability (ROE) and only the profitability variable has a significant effect.